ANALISIS KEMAMPUAN GEOMETRI SISWA SMA BERDASARKAN MOTIF TRADISIONAL PADA MATERI TRANSFORMASI GEOMETRI - Gamarina Isti Ratnasari (Jurnal Riset Daerah, 2025)
Geometric ability is one of the abilities needed for high school students. This ability affects students' ability to understand other mathematical topics. The purpose of this study was to analyze the geometry ability of high school students through traditional motifs. The type of research used was qualitative where the results of student projects were analyzed followed by interviews with students to dig deeper into students' geometry abilities. The subjects consisted of 108 students to work on the project and then 20 students were taken randomly for semi-structured interviews. Based on the results of the study, the results of the student level were in accordance with Van Hiele's theory where students were able to recognize geometric shapes, identify and analyze the properties of geometric shapes, and group shapes based on properties. Students also felt the benefits of this study such as getting to know more about transformations and their types,